2023
DOI: 10.1161/circoutcomes.122.009494
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns and Outcomes Associated With Anticoagulation Use Following Sepsis Hospitalizations With New-Onset Atrial Fibrillation

Abstract: BACKGROUND: Practice patterns and outcomes associated with the use of oral anticoagulation for arterial thromboembolism prevention following a hospitalization with new-onset atrial fibrillation (AF) during sepsis are unclear. METHODS: Retrospective, observational cohort study of patients ≥40 years of age discharged alive following hospitalization with new-onset AF during sepsis across 21 hospitals in the Kaiser Permanente Northern California health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Prior estimates using Medicare data have largely focused on the outpatient setting and demonstrate anticoagulant initiation rates for incident atrial fibrillation around 50% 3,4,12,13,40 . One recent study of patients in an integrated health system with incident inpatient atrial fibrillation associated with sepsis reported anticoagulant initiation rates of 20% 41 . Taken together with these studies, our results suggest that patients diagnosed with atrial fibrillation while admitted for other medical conditions—even those at high stroke risk—are infrequently initiated on anticoagulants or discharged with ambulatory cardiac monitors.…”
Section: Discussionsupporting
confidence: 56%
“…Prior estimates using Medicare data have largely focused on the outpatient setting and demonstrate anticoagulant initiation rates for incident atrial fibrillation around 50% 3,4,12,13,40 . One recent study of patients in an integrated health system with incident inpatient atrial fibrillation associated with sepsis reported anticoagulant initiation rates of 20% 41 . Taken together with these studies, our results suggest that patients diagnosed with atrial fibrillation while admitted for other medical conditions—even those at high stroke risk—are infrequently initiated on anticoagulants or discharged with ambulatory cardiac monitors.…”
Section: Discussionsupporting
confidence: 56%
“…Kosyakovsky et al [12] included many studies that were of low quality, had small samples and some lacked appropriate non-sepsis controls for comparison. This meta-analysis selected several most recent large cohort research [10,11,[47][48][49], among them, Jentzer et al provided the largest study so far (about 2.3 million hospitalized individuals) to exploring the relationship between sepsis and postdischarge cardiovascular complications according to a decade of nationwide follow-up data [11]. Given the in uence of confounding factors such as age, disease severity, and basic diseases, we adjusted for various confounding factors to the greatest extent possible and conducted multiple sensitivity analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Similar in ammatory cytokines were proven associated with the occurrence of long-term cardiovascular complications, and critical diseases are considered to induce immunometabolic changes in the relationship with atherosclerotic disease[58]. Wang et al [59] reported that people with long-standing atrial brillation(AF) have a trend to show higher levels of C-reactive protein than shorter duration AF, and under the interaction of AF and in ammation, the risk of thrombogenesis increases sharply during follow-up [10,47]. A randomized and double-blind trial shown that anti-in ammatory therapy targeting the interleukin-1β can signi cantly reduce the rate of recurrent cardiovascular events compared with placebo in post-myocardial infarction Kurematsu et al[64] found the health-related quality of life was signi cantly lower in sepsis survivors compared with nonsepsis survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The question of whether patients with sepsis and atrial fibrillation should receive anticoagulation therapy is still controversial ( 21 ).We observed that anticoagulant therapy effectively reduces 30-day mortality in septic and AF patients. Allan J Walkey et al proved that after hospitalization with new-onset AF during sepsis, oral anticoagulation use was uncommon and associated with potentially higher stroke/TIA risk ( 22 ). Umemura et al reported a meta-analysis showing that anticoagulant therapy could improve the mortality in sepsis-induced DIC patients.…”
Section: Discussionmentioning
confidence: 99%